2017
DOI: 10.17533/udea.iee.v35n2a02
|View full text |Cite
|
Sign up to set email alerts
|

Biosocial-academic profile and stress in first- and fourth-year nursing students

Abstract: Objective. To compare the biosocial and academic profile and stress levels between first-and last-year nursing students from a public university in Sao Paulo. Methods. This is an analytic and quantitative study. A biosocial and academic form and the instrument for Assessment of Stress in Nursing Students by Costa and Polak were applied to 83 students between February and March 2016. Results. Insufficient income and extracurricular activities contribute to higher levels of stress in both groups of students asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
16

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 6 publications
0
2
0
16
Order By: Relevance
“…Another possible explanation for this result is the clinical practice setting, since practical activities were conducted in public hospitals that were not as prepared for student reception as university teaching hospitals. Another study found that fourth-year students had higher mean scores in this domain, which is explained by the constant presence of these students in situations with greater demand for interaction with the multidisciplinary team, patients and families and the greater need for decision-making in this final phase of the course (16) . A study comparing nursing and medicine students found similar challenges and recommended improving the communication of these conflicts with professors and supervisors (17) .…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation for this result is the clinical practice setting, since practical activities were conducted in public hospitals that were not as prepared for student reception as university teaching hospitals. Another study found that fourth-year students had higher mean scores in this domain, which is explained by the constant presence of these students in situations with greater demand for interaction with the multidisciplinary team, patients and families and the greater need for decision-making in this final phase of the course (16) . A study comparing nursing and medicine students found similar challenges and recommended improving the communication of these conflicts with professors and supervisors (17) .…”
Section: Discussionmentioning
confidence: 99%
“…Assim, ao versar sobre o estresse no ambiente acadêmico, é preciso reconhecer o estudante na sua totalidade. 10,[14][15][16] Em relação aos domínios positivos, a maior média geral foi no domínio P4-equilíbrio, expressando que os estudantes se sentem confiantes para controlar aspectos importantes da sua vida. A autoconfiança, uma vez fortalecida, repercute no desenvolvimento de habilidades, crescimento pessoal e emocional para enfrentar situações diversas na graduação.…”
Section: Discussionunclassified
“…Cabe ainda salientar que houve maior presença de estresse e ansiedade entre os acadêmicos do primeiro, sexto, sétimo e oitavo periodo quando analisados separadamente. Bosso et al [20] constataram que, no primeiro ano, ocorre adaptação ao ambiente acadêmico como mecanismo de ensino-aprendizagem da instituição, formas de avaliação e novas responsabilidades, podendo levar a altos níveis de estresse e ansiedade. No estudo de Souza et al [21] sobre a qualidade de vida relacionada à saúde e sintomas depressivos de estudantes do curso de graduação em enfermagem, constatou-se que, no segundo e terceiro anos, ocorre o primeiro contato com o paciente, desencadeando crises de ansiedade, estresse, inquietações e aflições.…”
Section: Discussionunclassified